On point-dissipative systems of differential equations with quadratic nonlinearity - Anile K. Bose; Alan S. Cover; James A. Reneke (International Journal of Mathematics and Mathematical Sciences)
The system x′=Ax+f(x) of nonlinear vector differential equations, where the nonlinear term f(x) is quadratic with orthogonality property xTf(x)=0 for all x, is point-dissipative if uTAu<0 for all nontrivial zeros u of f(x).